Infestation of Xyleborus volvulus (Fabricius) (Coleoptera: Curculionidae: Scolytinae) in Mangifera indica L. (Mangifera: Anacardiaceae) in Manzanillo, Colima - Castrejón Antonio, Jesús Enrique; Montesinos Matías, Roberto; Tamez Guerra, Patricia; Fuentes Guardiola, Lucía Teresa; Laureano Ahuelican, Bruno; Arredondo Bernal, Hugo César (2018)
Ambrosia beetles are a natural part of the wood decomposition processes in ecosystems; however, some exotic species can cause serious problems in economically important crops, or seriously threaten native plant species (Sobel et al. 2015). Outstanding examples confirming this are the introduction of Xyleborus glabratus Eichhoff (Coleoptera: Curculionidae: Scolytinae) and Euwallacea sp. (Coleoptera: Curculionidae: Scolytinae) ambrosia beetles (Pisani et al. 2015), native to Asia, but introduced into the USA near Savannah, Georgia.